2003
DOI: 10.1097/00126334-200312010-00008
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Correlates of Discontinuation of the Initial HAART Regimen in an Urban Outpatient Cohort

Abstract: Gastrointestinal adverse events of HAART are the most frequently cited reason for discontinuation of HAART. An effort should be made to educate patients about these events and to encourage continued adherence. Additionally, appropriate prophylaxes for these events are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
152
3
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(176 citation statements)
references
References 28 publications
15
152
3
6
Order By: Relevance
“…1,7,[9][10][11][12][13][14] The most frequently reported side effects are gastrointestinal, including nausea, vomiting, and diarrhea. The ICONA study demonstrated that 25% of participants discontinued a HAART regimen by 1 year due to toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…1,7,[9][10][11][12][13][14] The most frequently reported side effects are gastrointestinal, including nausea, vomiting, and diarrhea. The ICONA study demonstrated that 25% of participants discontinued a HAART regimen by 1 year due to toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Concern regarding drug toxicity affects not only adherence to HAART regimens in patients being treated, but also may prevent some patients from initiating treatment. Bassetti and colleagues found that among their patients re- [1][2][3][4][5][6][7][8][9][10][11][12] fusing treatment with HAART, 19% feared side effects and 18% thought that the treatment regimen was overly complicated. 9 Improving patient education regarding the benefits of viral suppression and potential drug side effects and suggesting methods to help adhere to antiretroviral regimens are potential means of increasing initiation and decreasing discontinuation rates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Symptoms are common among individuals receiving HAART (Bonfanti et al, 2000;Lucas et al, 1999) and have been associated with both non-adherence (Ammassari et al, 2001;Chesney et al, 2000) and discontinuation of HAART (Mocroft et al, 2001;O'Brien et al, 2003). In order to develop appropriate interventions, several methodological issues need to be addressed.…”
Section: Introductionmentioning
confidence: 99%